Chemical analysis of mangrove land in north Aceh. Issue 1 (1st December 2022) - Harifia, R; Irham, M; Muhammadar,; Faisal,; Rusdi, M
Abstract: This study aims to determine the condition of water quality and the type of sediment fraction in the mangrove area around North Aceh in terms of physical and chemical parameters. Chemical analysis was carried out to test the content of heavy metals Pb, Cu, Cd, Hg, Fe and NH3, DO and physically analyzed to see the type and structure of sediment in addition to temperature, pH, brightness, and salinity in the mangrove area. This study used 3 sampling locations, namely the mangrove area around Pupuk Iskandar Muda (PIM), Lasloka, and Krueng Manee, 12 chemical and physical test parameters with a depth of 1-2.3 m for each sampling. The assessment was carried out through 2 stages of testing, namely in situ test, namely temperature, brightness, salinity, DO, pH. Meanwhile, ex-situ tests were carried out on TSS parameters, lead (Pb), copper (Cu), cadmium (Cd), iron (Fe), mercury (Hg) and ammonia (NH3 ). The results showed that almost all study areas exhibited that heavy metals were still below the permissible threshold except in the Krueng Manee area where the NH3, Cd and Hg tests showed values above the permissible or in a polluted state. The sediment characteristic analysis informed that round PIM and Krueng Manee is sandy loam dominated by Avicennia Sp mangroves and Loslaka area is muddy sand dominated by Rhizophora Sp mangrove species.